Self-Assembling Doxorubicin–Tocopherol Succinate Prodrug as a New Drug Delivery System: Synthesis, Characterization, and in Vitro and in Vivo Anticancer Activity - Duhem, Nicolas; Danhier, Fabienne; Pourcelle, Vincent; Schumers, Jean-Marc; Bertrand, Olivier; LeDuff, Cécile S; Hoeppener, Stephanie; Schubert, Ulrich S; Gohy, Jean-François; Marchand-Brynaert, Jacqueline; Préat, Véronique (Bioconjugate chemistry, 2014)
Self-assembled prodrugs forming nanoaggregates are a promising approach to enhance the antitumor efficacy and to reduce the toxicity of anticancer drugs. To achieve this goal, doxorubicin was chemically conjugated to d-α-tocopherol succinate through an amide bond to form N-doxorubicin−α-d-tocopherol succinate (N-DOX–TOS). The prodrug self-assembled in water into 250 nm nanostructures when stabilized with d-α-tocopherol poly(ethylene glycol) 2000 succinate. Cryo-TEM analysis revealed the formation of nanoparticles with a highly ordered lamellar inner structure. NMR spectra of the N-DOX–TOS nanoparticles indicated that N-DOX–TOS is located in the core of the nanoparticles while PEG chains and part of the tocopherol are in the corona. High drug loading (34% w/w) and low in vitro drug release were achieved. In vitro biological assessment showed significant anticancer activity and temperature-dependent cellular uptake of N-DOX–TOS nanoparticles. In vivo, these nanoparticles showed a greater antitumor efficacy than free DOX. N-DOX–TOS nanoparticles might have the potential to improve DOX-based chemotherapy.